Die uitdagings verbonde aan die lewering van primêre gesondheidsorgdienste in artikel 30-gebiede - Delene Mcnulty (AOSIS, 1981)
Article 30 areas are those in which the Department of Health, Welfare and Pensions act as the local authority in terms of health services. The Department has been developing comprehensive primary health care services, provided by registered nurses, in these areas since 1975. These services are challenged by complex problems and methods for primary health care used successfully in other areas are inappropriate. As those served are mostly immigrant farm labourers, village workers cannot be used. A lack of demographic and epidemiological data complicates the setting of objectives and thus planning of services. There are few clinic services and supportive services and sources for referral are inadequate or non-existent. The nurse mostly provides the service from a car at suitable central points. Sophisticated technology cannot be used and equipment, techniques and procedures must be carefully selected or even improvised. The success of the service depends on the nurses' ability to gain the co-operation and acceptance of the farmer who is the employer; doctors and pharmacists; school principals; magistrates; the nearest hospitals which may be in another country; and of the target group comprising the workers and their families. In this time of fragmentation and specialised care in health services the nurses providing the section 30 services must be able to meet all promotive, preventive, curative and rehabilitative health needs - she is expected to be a model of versatility.